2011
DOI: 10.1137/100803110
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Migratory Birds and Domestic Poultry and Its Role in Sustaining Avian Influenza

Abstract: Abstract. We investigate the role of migratory birds in the spread of H5N1 avian influenza, focusing on the interaction of a migratory bird species with nonmigratory poultry.The model is of patch type and is derived with the aid of reaction-advection equations for the migratory birds in the air along the flyways. Poultry may reside at some or all of the four patches of the model, which consist of the breeding patch for the migratory birds, their Winter feeding patch, and two stopover patches where birds rest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Galworthy et al described a slight delay in the migration because of the persistent infection28. Pre-immunization of wild birds with low pathogenic avian influenza is known to reduce the intensity of HPAI infection29, and is modeled in detail by Bourouiba et al23. Even though there are observations of low pathogenic viruses in wild birds in India1424 our model does not account for changes due to prior possible LPAI infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galworthy et al described a slight delay in the migration because of the persistent infection28. Pre-immunization of wild birds with low pathogenic avian influenza is known to reduce the intensity of HPAI infection29, and is modeled in detail by Bourouiba et al23. Even though there are observations of low pathogenic viruses in wild birds in India1424 our model does not account for changes due to prior possible LPAI infection.…”
Section: Discussionmentioning
confidence: 99%
“…A modeling study about disease dynamics in bar-headed geese Anser indicus indicated these wild bird populations suffer greater mortality during the autumn versus spring migration due to the higher number of outbreaks in the autumn22. Bourouiba et al (2011) also studied the interaction between poultry and migratory birds sustaining virus over long periods in China23. However, H5N1 viruses, if present, are thought to generally be at very low prevalence among migratory birds.…”
mentioning
confidence: 99%
“…advantages over that used in [6] and [3], where pausing locations are patches with time-periodic per-capita departure rates. That approach allows individual birds to spend varying amounts of time at pausing locations and does not capture the fact that in reality they stay together as one flock.…”
Section: Migratory Species With Diseasementioning
confidence: 99%
“…This was the approach in Gourley, Liu, and Wu [6] and Bourouiba et al [3], who calculated the arrival rate at a patch in terms of the departure rate from the previous patch at a previous time, using reaction advection equations to describe bird density for individuals en route between patches and to take account of flight speed and en route mortality. This approach does not perfectly capture the fact that in practice migratory birds stay together in large flocks to reduce energy cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation